Health education to the families of drug users: Establishing safe family conversations - Yeyentimalla, Yeyentimalla; Sera, Agnescia Clarissa (GHMJ (Global Health Management Journal), 2022)
This photo essay records a 5-hour health education session for the families of drug users in order to help them in establishing safe family conversations among the family members. After the discussion was over, the rundown included hospitality and dinner together. While enjoying the foods, the Panti residents joined the sharing session, and expressed their feelings missing their family and home. The residents want to connect hearts with their families. In the future, it is necessary to build a sustainable relationship for the success of the drug eradication program in our beloved country, Indonesia. Since the activity was held during the COVID-19 pandemic, the team also showed concern by providing masks to each participant.